2010
DOI: 10.1002/ajim.20877
|View full text |Cite
|
Sign up to set email alerts
|

Weekly work hours and stress complaints of workers in Korea

Abstract: Among males, VLWH are associated with a significant increase in stress, compared with SWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Shift work induces sleep problems (25). Furthermore, there is an increase in working hours with an increase in mental workload (26,27). Our data also showed that the prevalence of long working hours and having severe mental workload and the proportion of shift workers were the highest in the shorter sleep duration group.…”
Section: Discussionsupporting
confidence: 67%
“…Shift work induces sleep problems (25). Furthermore, there is an increase in working hours with an increase in mental workload (26,27). Our data also showed that the prevalence of long working hours and having severe mental workload and the proportion of shift workers were the highest in the shorter sleep duration group.…”
Section: Discussionsupporting
confidence: 67%
“…This same tendency was seen in Korea [36] and Norway [30], although the data indicating a relationship between lower educational level and long working hours in those two countries referred to ≥60 working hours/week.…”
Section: Discussionsupporting
confidence: 64%
“…In the Netherlands [29] and the United Kingdom [35], the groups with the highest educational level accounted for the greatest proportion of long working hours. In Korea, the result was different: among workers who reported excessively long working hours (≥60 h/week), professionals with lower educational levels predominated [36]. Among women in Norway, no association between long working hours and educational level was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth mechanism is psychosocial stress related to long working hours. Long working hours may produce high job stress that could increase the risk of cerebrocardiovascular disease 22,27,28) . Many previous studies of the association between overwork and cerebrocardiovascular disease have adjusted for other risk factors, including age, gender, past medical history, body mass index, behavioral habits, socioeconomic status, and work-related factors 4,29) .…”
Section: Discussionmentioning
confidence: 99%